2018
DOI: 10.1371/journal.pone.0194962
|View full text |Cite
|
Sign up to set email alerts
|

A correlation comparison between Altmetric Attention Scores and citations for six PLOS journals

Abstract: This study considered all articles published in six Public Library of Science (PLOS) journals in 2012 and Web of Science citations for these articles as of May 2015. A total of 2,406 articles were analyzed to examine the relationships between Altmetric Attention Scores (AAS) and Web of Science citations. The AAS for an article, provided by Altmetric aggregates activities surrounding research outputs in social media (news outlet mentions, tweets, blogs, Wikipedia, etc.). Spearman correlation testing was done on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 31 publications
4
66
1
2
Order By: Relevance
“…6 A study comparing the correlation of AAS and citations in the 6 PLOS journals showed no significant correlation for PLOS Medicine. 4 Our study extends beyond these findings by including the highest impact general medicine journals, which are expected to have the highest AAS for their articles due to wider audience. However, we could not comment on the effect of article accessibility (i.e., open versus closed access) on this association.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…6 A study comparing the correlation of AAS and citations in the 6 PLOS journals showed no significant correlation for PLOS Medicine. 4 Our study extends beyond these findings by including the highest impact general medicine journals, which are expected to have the highest AAS for their articles due to wider audience. However, we could not comment on the effect of article accessibility (i.e., open versus closed access) on this association.…”
Section: Discussionmentioning
confidence: 52%
“…AAS is increasingly used by journals as an integral article metric. While some studies have assessed the correlation between AAS and the number of citations in several disciplines and specialties, [1][2][3][4] it remains unclear whether AAS correlates with article citations among high-impact general medicine journals.…”
Section: Introductionmentioning
confidence: 99%
“…Correlations between altmetrics scores and citations have been found by Evans and Krauthammer (2011) for Wikipedia and by Thelwall et al (2013) for Twitter. However, the degree of correlation between WoS citation rates and AAS varies significantly from journal to journal and, as discussed by Huang, Wang, and Wu (2018), in most cases no clear relationship exists between them, which was also found for the CS papers.…”
Section: Alternative Metricsmentioning
confidence: 77%
“…Altmetric (Altmetric.com 2018) gives the WoS index, but also aggregates all online and non-technical references including "tweets" and downloads of articles, mentions in blogs, and mentions in the news media in its Altmetric Attention Score. In this score, mentions in the news media and blogs received most of the weighting compared to mentions in Twitter, Facebook, or YouTube (Huang, Wang, and Wu 2018).…”
Section: Alternative Metricsmentioning
confidence: 99%
“…In a large‐scale study, a significant correlation was found between six altmetric resources (tweets, Facebook wall posts, research highlights, blog mentions, mainstream media mentions and forum posts) and citation counts (Thelwall et al ). A recent study that covered six PloS specialized journals, revealed a significant positive correlation between the normalized altmetric scores and normalized citations (Huang et al ). The number of Twitter mentions can forecast highly cited articles within the first 3 days of their publication (Eysenbach ).…”
Section: Introductionmentioning
confidence: 99%